Child protection versus teacher protection: a legal review of the settlement of school corporal punishment in Indonesia - Windari, Rusmilawati (Crime, law and social change, 2021)
The education sphere nowadays faces the issue of corporal punishment, which is considered a detrimental school discipline that has negative impacts on a child’s development and growth. Teachers are advised to always opt for moral persuasion rather than corporal punishment in disciplining their misbehaving students. In Indonesia, the teacher stays in a dilemma as many cases of the administration of light corporal punishment have gone to criminal litigation and ended up with sentencing of the teacher. Concurrently, often the teacher becomes a victim of a student’s disruptive behavior when they only adopt soft measures such as reprimands. Legal protection for teachers has been guaranteed by the Teacher and Lecturer Law Year 2005 and several other relevant regulations. Unfortunately, the existence of the Law on Child Protection Year 2014, which broadly governs the prohibition of violence, has made criminalisation of teachers easy and their protection questionable. This paper elaborates the extent of legal protection provided to teachers in the term of facing criminal litigation due to corporal punishment. It also explores the legal effort that can be undertaken by the Indonesian Government to embody fair protection for teachers and children.